A PROTRAIT PARTICIPATION IN DECISION MAKING AMONG ACCOUNTING LECTURES IN YOGYAKARTA - Sukirno . (LPMPP Universitas Negeri Yogyakarta, 2013)
Abstract: As a developing country, Indonesia has been facing problems regarding finding the ways how to improve her higher education quality. In this study, lecturer participative decision making (hereafter abbreviated, PDM)) is observed and analysed to be linked with lecturer satisfation, commitment, and performance.Mail survey was used to collect the data. Open-ended questionnaires were distributed to the accounting lectures at faculty of economics and business in Yogyakarta Special Region, Indonesia. A total of 61usable packets of questionnaires were obtained by dual rater approach. Data were analyzed by employing tabulation, anovaandregressionanalysis.It is found that lecturer participation will increase lecturer performance. Nevertheles, lecturer participation is beyond the track of getting lecturer satisfaction and lecturer commitment. Lecturer participation may be useful to boost lecturer commitment based on the single rating. In response jangling results, theoritical and empirical discussion are presented to provide useful academic and managerial recomendations. Keywords: participative decision making, higher education, Indonesia POTRET PARTISIPASI DOSEN AKUNTANSI DALAM PENGAMBILAN KEPUTUSAN DI INDONESIA Abstrak: Sebagai negara berkembang, Indonesia menghadapi persoalan erkait dengan peningkatan kualitas pendidikan tinggi. Penelitian ini bertujuan untuk mengamati, mendeskripsi dan menganalisis partisipasi dosen dalam pengambilan keputusan dan pengaruhnya terhadap kepuasan, komitmen, dan kinerja dosen. Survei menggunakan angket semi terbuka dengan menggunakan rater ganda dilakukan untuk mengumpulkan data penelitian. Sejumlah 61 dosen akuntansi dari berbagai fakultas ekonomika dan bisnis di Daerah Istimewa Yogyakarta berpartisipasi dalam penelitian ini. Data yang diperoleh dianalisis dengan menggunakan tabulasi, Anova test dan analisis Regresi. Hasil penelitian berbasis pada single rating menunjukkan partisipasi dosen dalam pengambilan keputusan berpengaruh terhadap kinerja dosen, namun demikian partisipasi dosen tidak terbukti berpengaruh terhadap kepuasan dan komitmen dosen. Kesimpulan yang berbeda atas hasil analisis dalam penelitian ini didiskusikan dan dipresentasikan agar dapat dibuat rekomendasi akademik dan managerial yang berguna. Kata Kunci: pengambilan keputusan partisipatif, perguruan tinggi, Indonesia